1995
DOI: 10.1149/1.2049984
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Metal Oxides as a Model for the Electronic Properties of Passive Films

Abstract: The aim of the present work is to compare the electronic properties of natural passive films on iron and chromium with sintered bulk metal oxides. The characterization of the semiconductive properties of various bulk oxides shows that the passive film on iron can be simulated by highly doped Fe2O3 . The doping concentration of Fe‐oxides is determined by their Fe2+ content. At a dopant level of ≈5 · 1020 cm−3 in Fe2O3 the flatband potential, bandgap energy, intensity of the photocurrent, and the doping conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 4 publications
3
38
0
3
Order By: Relevance
“…In such a case further information gathered by other (possibly in situ) analytical techniques are necessary to rationalise PCS data of passive films. Other authors [167][168][169] have proposed a different route for the identification of passive film. According to these authors a comparison of PCS data (as well as of the general semiconducting behavior) between passive films anodically grown and sputtered oxides could help to identify the nature of passive films.…”
Section: (V) Pcs Analysis Of Passive Films and Corrosion Layers On Bamentioning
confidence: 99%
“…In such a case further information gathered by other (possibly in situ) analytical techniques are necessary to rationalise PCS data of passive films. Other authors [167][168][169] have proposed a different route for the identification of passive film. According to these authors a comparison of PCS data (as well as of the general semiconducting behavior) between passive films anodically grown and sputtered oxides could help to identify the nature of passive films.…”
Section: (V) Pcs Analysis Of Passive Films and Corrosion Layers On Bamentioning
confidence: 99%
“…11, the photocurrent spectra of coated EP-Al samples differred greatly from that of bare EP-Al sample because of the onset of a large photocurrent contribution in the region of wavelengths around 300 nm. It has been reported that photocurrent spectra of chromium oxides passive films show maxima 16,17 in the same wavelength range. By assuming the presence of nondirect ͑indirect for crystalline materials͒ optical transitions between valence band ͑VB͒ and conduction band ͑CB͒ of a CCC, and a direct proportionality between the photocurrent yield, I ph , ͑see above͒ and the light absorption coefficient ␣, 12 the following equation holds…”
mentioning
confidence: 97%
“…This behavior is also reminiscent of analogous behavior of Cr passive films. 16,17 In order to determine the flatband potential, V FB , for the different films we used two different approaches depending from the fact that the blocking region of the I tot vs. U E plots was more or less wide. In fact in some cases the inversion photocurrent potential was accessible by recording the I ph vs. U E plots at different , before the increase of the total current ͑see Fig.…”
mentioning
confidence: 99%
“…The electrochemical micro cell was connected to an Autolab PGStat30 Potentiostat from Metrohm and for further data processing to a computer [19]. The EIS measurements were carried out with perturbation amplitude of ±10 mV in a frequency range from 100 KHz to 10 mHz.…”
Section: Exprimentalmentioning
confidence: 99%
“…Manuscript received Aug. 16,2011; revised Jan. 19,2012. Dechema e.V., Theodor Heuss-Allee 25, D-60486 Frankfurt, Germany E-mail : Tesfu@dechema.de, T.Tesfu@gmx.de…”
Section: Introductionunclassified